Factors influencing residents' attitude towards marine resource utilization in Tun Sakaran Marine Park, Malaysia - Mohd Yusah, Habibah; Shuib, Ahmad; Kunasekaran, Puvaneswaran; Nordin, Nurul Afifah (Universiti Malaysia Sarawak, 2018)
Communities living in the Tun Sakaran Marine Park (TSMP) depend on the marine resources for their livelihood. The marine park is managed by state government, the Sabah Parks, with the main objective of conserving the high marine biodiversity in the area. The communities living in the area use the resources on a daily basis, for family consumption and subsistence. The marine park is also popular for its world class diving sites which has contributed to the growth of the ecotourism industry. The main objective of this study is to determine the sociodemographic characteristics of the resident communities in order to evaluate the factors that determine the attitude of the communities towards the utilization of the marine resources. Data from 116 respondents in three islands in the park were collected using the convenient sampling method. Results of the regression analysis showed that citizenship (non-citizen), education, sense of ownership to the place and responses towards destructive fishing methods had significant influences on the attitudes towards the utilization of the marine resources. Relevant agencies can help to improve the attitudes of the communities by increasing awareness of the communities through informal education and providing extension information to reduce uses of destructive fishing methods.